PORE PRESSURE MODELLING IN A COMPRESSIONAL SETTING: A CASE STUDY FROM ASSAM, NE INDIA. (11th June 2019) - Dasgupta, S.; Chatterjee, R.; Mohanty, S. P.; Alam, J.
Abstract : The petroleum‐bearing Assam oil province, NE India, has a complex tectonic history resulting from the Cenozoic collision of the Indian Plate with the Eurasian and Burma Plates. Well data show that there are significant variations in the magnitude and stratigraphic occurrence of overpressures across the foreland basin. In areas which have not been affected by thrust tectonics, analyses of pore pressures in Upper Miocene to Eocene and underlying sequences indicate that overpressures are caused by disequilibrium compaction. Pore pressures were observed to be 25.8–28 MPa over a depth interval of 2259–2382 m and 43–45 MPa between depths of 3820 m and 3994 m. In the adjacent Schuppen (fold‐thrust) belt, multiple overpressure regimes are recognised and disequilibrium compaction is the main cause of the overpressures in both the supra‐thrust and the sub‐thrust successions. Unloading due to uplift and erosion in the supra‐thrust section of the Schuppen belt was quantified using velocity data and the normal compaction trend for shales; net uplift was estimated to total 1000–1600 m with a standard deviation of 250–476 m. Overpressure development in supra‐thrust strata in the Schuppen belt suggests the possible effects of normal burial prior to tectonic deformation, as well as of compaction related to high horizontal stresses resulting from thrusting and associated fold development. Pore pressures in the supra‐thrust section, over a depth interval of 700–1400 m which corresponds to the Oligocene to Upper Miocene succession, were observed to range from 9.6 to 19.5 MPa. The top of the overpressured zone in sub‐thrust strata was observed in the Upper Eocene to Oligocene succession at a depth of 3700 m, in the argillaceous Barail Formation, with pore pressures ranging between 48 MPa and 54 MPa. Pore pressures were estimated using acoustic log data calibrated to measured pressures from Modular Dynamic and Drill Stem Test data. The modelled pore pressures closely correspond to the measured data, supporting the robustness of the model. The numerical parameters defined in this study may be used for future exploration in the region.